Place attachment and environmental awareness predict university students’ pro-environmental behavior - Dessy Nur Utami; Nurul Sih Widanti; Triana Wulandari (Universitas Trunojoyo Madura, 2026)
Universities contribute significantly to promoting environmental sustainability by fostering eco-friendly mindsets and behaviours among students. In line with this role, the present study investigated the connections among place attachment, environmental consciousness, and pro-environmental actions in college students. An explanatory method utilizing surveys was employed in the study. Data were gathered via online surveys sent to 114 students at Universitas Hang Tuah by accidental sampling. Three psychological tools were employed to evaluate pro-environmental behaviour, attachment to place, and awareness of the environment. Data analysis was performed utilizing Spearman’s rank correlation with the support of IBM SPSS Statistics version 25. The results indicated a significant positive relationship between place attachment and pro-environmental behaviour (r = 0.414, p 0.01), as well as a robust connection between environmental awareness and pro-environmental behaviour (r = 0.516, p 0.01). Furthermore, there was a positive correlation between place attachment and environmental awareness (r = 0.384, p 0.01). Descriptive results showed that most students exhibited moderate levels of environmental behaviour, attachment to place, and awareness of environmental issues. These findings suggest that emotional attachment to the campus environment and environmental awareness are closely related to environmentally responsible behaviour among university students. It is suggested that future research investigate more psychological and social elements affecting pro-environmental behaviour, including social norms, environmental values, and support from institutions.